Monitoring of Insecticides resistance against cotton Jassid (Amrasca biguttutla biguttutla) under laboratory conditions - Javed,Z. (2023)
Abstract Development of insecticides resistance mainly hinge with managements techniques for the control of Jassid, Amrasca biguttutla biguttutla. Five insecticides were applied against field collected and laboratory rared jassid populations during the years of 2017 to 2019 to profile their resistance level against field population of jassid through leaf dip method. Very low resistance level was found in jassid against confidor whereas high level of resistance was observed by pyriproxyfen against other test insecticides. Gradual resistance was observed against diafenthiuron. It is concluded that for the management of Jassid repetition of same insecticide should be avoided. The use of confidor may be reduced to overcome resistance against Jassid.